Forced Defense in Indonesia: Striking a Balance between Proportionality and Subsidiarity - Handy Ariansyah; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aimed to assess the compliance of the decision made by the Kepanjen District Court Number 1 /Pid.Sus-Child/2020/Pn Kpn with the provisions of criminal law book of article 49 paragraph 1 and paragraph 2, which govern forced defense as a means of self-defense. Using the normative method, the study examined legal literature to establish the truth of the matter. The study found that a forced defense must adhere to the principles of proportionality and subsidiarity to be considered legitimate. The conclusion drawn from this study is that the decision of the Kepanjen District Court must be evaluated based on these two requirements to establish the legal truth of the matter. Highlights: Proportional and subsidiarity requirements are essential for a forced defense to be considered legitimate. Excessive actions that go beyond the threat faced may not be considered a forced defense. The actions of the victim must be considered in evaluating the legitimacy of a forced defense.